Le rôle des clichés et des stéréotypes dans la construction de l’image de la femme dans Les Années d’Annie Ernaux - Takács, Petra (Verbum – Analecta Neolatina, 2022)
Annie Ernaux’s Les années is one of the best examples for the exploitation of clichés and stereotypes in contemporary French impersonal autobiographies. Clichés and stereotypes, thanks to their “double property”, to use the expression of R. Amossy and E. Rosen, are able to both create and destroy referential illusion, which lends to the text the capacity to present and question its subject at the same time. With clichés and stereotypes, the text offers multiple subjects to analyse, one of which is the image of women and the female condition. In the present study, we aim to discover how clichés and stereotypes contribute to presenting and denouncing the female stereotypes used by the text.